Challenges of Top-Down Policy as Stakeholder Engagement Strategy in the Implementation of Internal Quality Assurance in Higher Education Institutions: An Empirical Research - Dewi, Yustina Erti Pravitasmara; Sugiharto, Dwi Yuwono Puji; Utami, Intiyas; Huruta, Andrian; Sundari, Ocky (Technium Social Sciences Journal, 2021)
Higher education plays a significant role in shaping the future national competitiveness. In Indonesia, its governance drives a massive transformation and is more focused on the internal quality assurance over the external one. There are several changes from aspects related to the implementation of internal quality assurance system, especially on the transformation of higher education which faces internal challenges that consider the managerial-based work as a highly complex and heavy-duty work and is less relevant to individual achievement. Further, the biggest challenge in implementing a quality management is the lack of stakeholder management. It gets worse with the top-down policy being implemented to improve the quality of higher education. This present study gives an overview of the internal quality assurance of higher education institutions experiencing challenges in stakeholder management and their top-down-policy-based initiatives. There was a total of 67 private universities in Central Java, Indonesia involved in this study. The data was collected in April – July 2019 using questionnaire and focus group discussion (FGD). The FGD involving the executives of the quality board of each university discussed the implementation of new quality assurance regulations. The results show a consistency of the respondents who apparently had incomplete documents of internal quality assurance, followed by skepticism about the future of institution which simultaneously affected the policy in the future.